Pembuatan Penggantung Pakaian Bahan Kawat Aluminium Diameter 3 mm, Panjang 45 cm, Kapasitas 50 Biji/Jam (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The general metal clothes hanger that is still made manually is not strong enough as a problem faced. The purpose of making is to obtain a clothes hanger made of aluminum wire with a diameter of 3 mm with a length of 45 cm that is light and strong enough. The manufacturing method includes: clothes hanger design, making a bender in the form of a jig from semi-automatic clothes bending steel, preparing raw materials for AA1100 type aluminum wire with a diameter of 3 mm, preparing bending tools and labor, cutting 3 mm diameter wire with a length of 100 cm, bending the wire into a clothes hanger, finishing according to orders painted or anodized or left in natural color, quality and dimension inspection, and packaging. The manufacturing results are clothes hangers made of aluminum wire with a diameter of 3 mm, a length of 45 cm weighing 150 g which can withstand a load of around 2 kg, a total production cost of IDR 2319/unit, and a process duration of 72 seconds/unit which implies that the manufacturing is feasible to be applied to small and medium scale industries or businesses.